Defense mechanisms in immune-mediated diseases: a cross-sectional study focusing on Severe Allergic Asthma and Hymenoptera Venom Anaphylaxis patients - Martino, Gabriella; Di Giuseppe, Mariagrazia; Silvestro, Orlando; Vicario, Carmelo Mario; Giorgianni, Concetto Mario; Ruggeri, Paolo; Sparacino, Giorgio; Juli, Maria Rosaria; Schwarz, Peter; Lingiardi, Vittorio; Lo Coco, Gianluca; Gangemi, Sebastiano; et al. (Frontiers in Psychology, 2025)
BackgroundChronic immune-mediated diseases, such as Severe Allergic Asthma (SAA) and Hymenoptera Venom Anaphylaxis (HVA), significantly impact quality of life. Defense mechanisms, as implicit emotion-regulation strategies, shape an individual’s adaptation to chronic stressors. This cross-sectional study explored the relationship among defensive functioning, psychological symptoms, and perceived physical and mental health in patients with SAA and HVA.MethodsTo explore the role of defensive functioning in perceived physical and mental health 34 patients with SAA and 32 with HVA were assessed with the Short-Form Health Survey, the Beck Depression Inventory, the Hamilton Anxiety Rating Scale, the Toronto Alexithymia Scale, and the Defense Mechanisms Rating Scales Self Report-30; between-group differences, and mediation analyses were performed.ResultsDefensive functioning was positively associated with mental health and negatively related to depressive symptoms, anxiety and alexithymia. Males reported significantly higher physical and psychological health than females. Patients with SAA exhibited significantly higher defensive functioning but worse physical health than HVA patients. Mediation analysis revealed that defensive functioning correlated with disease type and physical health, accounting for 39% of the explained variances. Moreover, defensive functioning independently predicted mental health.ConclusionThis study highlights the influence of implicit emotional regulation on psychophysiological well-being in patients with chronic immune-mediated disorders. Despite reporting lower perceived physical health, patients with SAA exhibited higher defensive functioning, suggesting that chronic conditions may shape distinct psychological adaptation processes. These findings support the importance of defence mechanisms assessment to tailor psychological interventions promoting well-being in patients with chronic diseases.